2017
DOI: 10.3389/fimmu.2017.01621
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Non-Signalling Chemerin Receptor CCRL2 Exacerbates Acute Inflammatory Responses In Vivo

Abstract: Chemerin is a chemotactic protein that induces migration of several immune cells including macrophages, immature dendritic cells, and NK cells. Chemerin binds to three G protein-coupled receptors (GPCRs), including CCRL2. The exact function of CCRL2 remains unclear. CCRL2 expression is rapidly upregulated during inflammation, but it lacks the intracellular DRYLAIV motif required for classical GPCR downstream signalling pathways, and it has not been reported to internalise chemerin upon binding. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…This receptor is also engaged in the regulation of immune cell recruitment, to dampen an acute inflammatory response. Mice that lack CCRL2 have an exacerbated acute inflammatory response to peritonitis and have increased neutrophils and monocytes in the peritoneal cavity [200].…”
Section: Chemerin and Immune Functionmentioning
confidence: 99%
“…This receptor is also engaged in the regulation of immune cell recruitment, to dampen an acute inflammatory response. Mice that lack CCRL2 have an exacerbated acute inflammatory response to peritonitis and have increased neutrophils and monocytes in the peritoneal cavity [200].…”
Section: Chemerin and Immune Functionmentioning
confidence: 99%
“…Taken together, these results support a role for CCRL2 in the regulation of CXCR2-mediated inside-out β2-integrin activation ( Del Prete et al, 2017 ). Using different models of acute inflammation induced by zymosan and thioglycolate, Regan-Komito et al (2017) reported that Ccrl2-deficient mice expressed an exacerbated phenotype characterized by increased neutrophils infiltration associated to increased local and systemic levels of chemerin and CXCL1. It is possible that different experimental conditions might be responsible for this apparently contrasting phenotype.…”
Section: Role Of Ccrl2 In Inflammatory Diseasesmentioning
confidence: 99%
“…Zymosan induced peritonitis (using 100 ug of zymosan) is a model of acute inflammation characterised by the recruitment of myeloid cells to the peritoneum following injection of zymosan, that is largely resolved after 48-96 h (Regan-Komito et al, 2017). To test if pharmacological inhibition of BTK with the FDA/EMA approved BTK inhibitor ibrutinib would reduce myeloid cell recruitment during acute inflammation C57BL/6 mice were pre-treated with ibrutinib (0.1 -10 mg/kg; p.o.)…”
Section: Resultsmentioning
confidence: 99%